HPV integration profiling using nanopore sequencing and association with cervical precancerous lesion - Hou, Ying; Ni, Shoufeng; Liu, Xin; Liu, Xingyu; Wang, Nan; Xu, Fuqiang; Gao, Jianyong; Li, Yanmei; Zhou, Yuxiang; Tang, Huadong; Bian, Meina; Li, Xiulan; et al. (Frontiers in Microbiology, 2025)
ObjectivesHPV infection and HPV DNA integration can lead to cervical cancer, but the relationship with lesion severity is unclear. This study aimed to investigate the correlation between HPV integration profile and cervical lesion extent.Materials and methodsTwenty patients representing cervicitis, CIN I, CIN II, and CIN III underwent nanopore sequencing for HPV genotype and integration site analysis. HPV integration profiles were correlated with lesion severity. Gene Ontology (GO) and KEGG analysis were used to identify stage-specific genes and pathways.ResultsHPV integration rates were 60, 60, 100, and 100% for cervicitis, CIN I, CIN II, and CIN III, respectively, with varying numbers of integrated genes. Each group had specific stage-related genes, with 83 shared genes linked to neuron development and cell–cell processes. CIN II and CIN III displayed more cancer-related pathway enrichment than earlier stages.ConclusionA positive correlation exists between HPV integration frequency and cervical lesion stage. Late-stage lesions showed heightened enrichment in cancer-related pathways through specific HPV-integrated genes.